Validation of a questionnaire on learning through ICT and its Effect on University Students’ Wellbeing During COVID-19 - Suárez-Monzón, Noemí (2022)
Covid-19 virus presence in most countries of the world has lead to an overuse of information and communication technologies (ICT) during training processes. This has made it possible to continue studies in different conditions than the ones experienced in 2019, now in compulsory social isolation and home study environments. This article aims to design and validate an instrument that allows measuring learning by information technologies and its effect on the welfare of university students who assist to online education. Authors began with a documentary analysis for the construction of the theoretical framework and then, the validity of the instrument is checked in a pilot sample of 1952 students. The result was an instrument with a Crombach’s alpha of 0.8. It is concluded that the instrument can be applied in studies related to similar problematic situations.